2017
DOI: 10.1111/jop.12652
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the genes for keratin‐4 and keratin‐13 in Swedish patients with white sponge nevus

Abstract: We describe a novel heterozygous missense mutation in the keratin-4 gene of a Swedish family with white sponge nevus. Our results support the notion that mutations in keratin-4 and keratin-13 are the underlying cause of white sponge nevus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…When chromosomes in recipient cells have homogenous genes with mutation sites, both of their expressions are inhibited, leading to the so‐called cosuppression effect. Additionally, the transgene may be inactivated when homogenous genes are normally expressed …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When chromosomes in recipient cells have homogenous genes with mutation sites, both of their expressions are inhibited, leading to the so‐called cosuppression effect. Additionally, the transgene may be inactivated when homogenous genes are normally expressed …”
Section: Discussionmentioning
confidence: 99%
“…19 The study by Jorgenson and Levin confirmed the discrete expression of KRT4, and WSN patients from their family fit the rule of autosomal dominant inheritance. 4 There is a 50% chance for the children of WSN patients to develop the same disease. Theoretically, the positive rate for F1 generation of KRT4 transgenic mice should be 50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…White sponge nevus (WSN) is a rare hereditary condition characterized by thickened white spongy plaques of the mucous membranes 1 . It is commonly known as a congenital condition; however, it often does not develop in childhood 2…”
Section: Figmentioning
confidence: 99%